On-line analysis of free-tropospheric water-soluble acidic gases and particulate anions on the summit of Mt. Fuji, Japan. (15th March 2022) - Takeuchi, Masaki; Tomiyasu, Naoya; Namikawa, Makoto; Tanaka, Hideji; Toda, Kei; Katsumi, Naoya; Okochi, Hiroshi
Abstract: Atmospheric gaseous and particulate pollutants emitted from local or regional sources cause transboundary air pollution. To better understand this environmental issue, it is useful to monitor the free troposphere, reflecting the global air quality, with high temporal resolution. During the summer of 2016, we operated an original on-line monitor on the summit of Mt. Fuji, Japan (3776 m a.s.l.) to measure water-soluble acidic gases and particulate anions in the free troposphere. Mt. Fuji is a free-standing mountain and, therefore, hardly affected by air pollutants emitted from the local region. The lab-made gas/particle collector coupled ion chromatograph successfully provided meaningful data on an hourly basis. The average concentrations of HNO3, SO2, NO3 −, and SO4 2− ( n = 64 each) were, respectively 1.8 ± 0.9, 2.3 ± 2.5, 0.22 ± 0.16, and 3.9 ± 2.6 nmol m −3 . The gaseous HNO3 was the predominant form compared to particulate NO3 − . For the sulfur component, the percentage of particulate form was higher than that of the gaseous one. The high time-resolution monitoring enabled us to classify the observed data based on the air parcel inflow direction to the sampling point even when it changed dramatically. As a result, the oxidation of SO2 to SO4 2− in atmospheric transport can be discussed for each air parcel. It was suggested that the SO2 oxidation was enhanced in the air parcels that passed over the Asian Continent. Graphical abstract: Image 1 Highlights: Free-tropospheric acidic gases and particulate anions were monitored at the summit of Mt. Fuji (3776 m a.s.l.), Japan. Mt. Fuji is a free-standing mountain and was considered hardly influenced by local pollution. The gas/particle monitoring system automatically provided valuable data on the acidic gases and particulate anions on an hourly basis. High temporal-resolution observations have effectively identified the sources of long-range transported air pollutants.